Teaching problems related to the blackboard learning management system in teaching practical courses at the College of Science at Taibah University - Alhusaini, Sara Awwad (Journal of Curriculum and Teaching Methodology, 2022)
The research aims to identify the teaching problems related to the blackboard learning management system in the teaching of practical courses in the Colleges of Science at Taibah University from the point of view of faculty. The researcher used the descriptive method (survey), and to achieve the research objectives prepared the resolution tool consisting of (7) domains, and applied to (160) faculty members in the colleges of science departments (physics, chemistry, biology, geology) Cronbach’s alpha coefficient was used to measure internal coherent. Frequencies, percentages, arithmetic averages, t- test and one way ANOVA were used. The results of the research found teaching problems facing faculty when teaching practical courses through the system to a high degree, and the teaching problems related to students came first from the degree of existence while the teaching problems related to content were in the last place, and found statistically significant differences in some domains for females by gender variable and for those with medium skill in using computers According to the computer skill variable, and the lack of statistically significant differences depending on variable (section- scientific rank- experience- branch- number of computer- related training courses) were in all domains. The researcher came up with several recommendations, the most important of which was continuous needs analysis of the needs of faculty to meet their needs and intensify training courses for them to use teaching strategies and calendar methods appropriate to the system.